A comprehensive database of tests on axially loaded piles driven in sand - Yang, Zhongxuan; Jardine, Richard, 1953-; Guo, Wangbo; Chow, Fiona (Academic Press is an imprint of Elsevier, 2015)
A Comprehensive Database of Tests on Axially Loaded Driven Piles in Sands reviews the critical need to develop better load-test databases for piles driven in sands. The key quality parameters, population of current entries and reporting formats are described before offering preliminary results obtained from comparisons between axial capacities calculated by various predictive approaches and site measurements. This book also shows that the "simplified" and "offshore" ICP and UWA variants proposed by some practitioners are over-conservative and that their use could be discontinued. The new pile capacity and stiffness database offers a broad scope for evaluating potential prediction biases relating to a wide range of soil and pile parameters. Submission of further high quality tests for inclusion in regularly updated versions is encouraged. Presents a comprehensive and updated database for piles driven in predominantly silica sandsFeatures reviews of the design procedures for driven piles in sandAssesses the performance of various mainstreams design procedures applied for driven piles in sandProvides comprehensive information of case histories of pile load tests